CHRONIC LOW BACK PAIN: CORRELATION BETWEEN KINESIOPHOBIA AND DISABILITY (Fiep Bulletin - online, 2013)
Introduction: Low back pain has a high prevalence, etiology multidimensional and has important negative impact, both in the physical, social and psychological. Objective: To correlate the level of disability and kinesiophobia controlled performance in the six-minute walk test (6MWT). Methodology: The study included 12 subjects with chronic low back pain, four men and eight women, aged between 28 and 59 years. The kinesiophobia levels were assessed by the Scale Cover kinesiophobia. Functional disability was measured by the Oswestry Disability Index. Functional capacity was evaluated by the six-minute walk test (6MWT). Correlations were made ??by partial correlation test, controlled by the 6MWT. Results: There was no correlation between levels of disability and kinesiophobia (partial correlation controlled performance on the 6MWT = 0.479, p = 0.105). Conclusion: There were no correlations between levels of kinesiophobia and disability. The correlation did not change when controlled by the 6MWT.
Keywords: Low back pain; functional disability; TC6